1999
DOI: 10.1021/ja991664f
|View full text |Cite
|
Sign up to set email alerts
|

NO Disproportionation Reactivity of Fe Tropocoronand Complexes

Abstract: The synthesis and characterization of divalent 5)] (1) and trivalent [Fe(OTf)(TC-5,5)] (2) tropocoronand complexes are described. Compound 1 reacts with 1 equiv of NO to form the {FeNO} 7 complex 3. A single-crystal X-ray structure determination of 3 reveals a trigonal bipyramidal geometry with a linearly coordinated nitrosyl (Fe-N-O ) 174.3(4)°) having a short Fe-N distance of 1.670(4) Å. EPR and Mo ¨ssbauer spectroscopy, SQUID susceptometry, and normal coordinate analysis indicate 3 to be a low-spin {Fe III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 56 publications
14
117
4
Order By: Relevance
“…The OϪSϪC angles [104.08 (20)°] are also average for corresponding angles found in the literature for 400 related metalϪsulfoxide complexes and less than that in free dmso [105.7(2)°], whereas the CϪSϪC bond angles (Table 3) are almost similar to the corresponding values in free dmso (98.6°). [25] The perchlorate anions are not coordinated to the central Co II ion and therefore they are not reported in Figure 4.…”
Section: Structural Datasupporting
confidence: 64%
“…The OϪSϪC angles [104.08 (20)°] are also average for corresponding angles found in the literature for 400 related metalϪsulfoxide complexes and less than that in free dmso [105.7(2)°], whereas the CϪSϪC bond angles (Table 3) are almost similar to the corresponding values in free dmso (98.6°). [25] The perchlorate anions are not coordinated to the central Co II ion and therefore they are not reported in Figure 4.…”
Section: Structural Datasupporting
confidence: 64%
“…However, the first, direct structural insight concerning the g ϭ 2.03 family has been obtained with a bis-imidazole-coordinated complex mimicking histidine residues (34). In addition, some mononitrosyl-iron complexes containing nitrogen donor ligands also exhibit these types of EPR features (35,36). Recent data concerning the nature of the ligands coordinated to iron in FeFur are much more in agreement with the environments in these compounds.…”
Section: Discussionmentioning
confidence: 93%
“…UV-visible spectra (not shown) revealed three bands at 310, 365, and 400 nm, characteristic of charge-transfer bands observed with small NO-iron complexes (35)(36)(37)(38). The appearance of these bands grew in parallel with the increase of the EPR signal intensity.…”
Section: No Binds To Fe II In Fefur To Form a S ‫؍‬ 1͞2 Dimeric Speciesmentioning
confidence: 95%
See 1 more Smart Citation
“…This purpose is very important in chemical, biochemical, biological, environmental and industrial fields [6][7][8] . For example, Co(II) and other metal complexes play an important role in the industrial cleaning of gaseous effluents from power plants through the suggested simultaneous absorption of nitric oxide and sulfur dioxide [9][10][11] . Furthermore, the binding, transport and activation of molecular oxygen by metal complexes is a topic of wide current interest due to the many implications that such metal containing systems have in both biomimetic and abiotic processes involving dioxygen 12 .…”
Section: Introductionmentioning
confidence: 99%